Periglacial landforms in the high Drakensberg, Southern Africa: morphogenetic associations with rock weathering rinds and shrub growth patterns. Issue 3 (3rd July 2021) - Grab, Stefan; Knight, Jasper; Mol, Lisa; Botha, Tamara; Carbutt, Clinton; Woodborne, Stephan
ABSTRACT: Here, we aim to establish possible morphogenetic associations between periglacial phenomena (sorted circles and turf-/stone-banked lobes) by examining (a) rock surface weathering rinds by thin section microscopy and SEM-EDX analysis, and (b) alpine shrub growth patterns of Helichrysum trilineatum supported by AMS 14 C age determination. The study area is the Mafadi–Njesuthi summit zone, one of the highest alpine regions of southern Africa. Rock weathering results indicate that clasts in large sorted circle centres experience high chemical weathering rates on both exposed (upper) and non-exposed (lower) surfaces, whereas clasts in lobes and very large apparently 'relict' sorted circles have been inactive for a prolonged period of time, based on strongly contrasting weathering rates on both exposed and non-exposed clast surfaces. Large sorted circles originating from a previous (possibly Last Glacial Maximum or late-glacial) colder period are still marginally or episodically active, thus restricting plant succession on these landforms. Even where very large sorted circles and turf-/stone-banked lobes are inactive, their legacy continues, as expressed in today's surface morphology, and still influence ground abiotic conditions through the generation of microrelief and microclimate which in turn have impacts on ecosystem patterns including the distribution of H. trilineatum . Such shrub growth patterns are influenced by microscale site morphology, associated abiotic controls, and ongoing seasonal cryogenic activity. Both active and inactive periglacial landforms on highest summits of the Drakensberg represent microscale environments with distinct fine-scale abiotic and geomorphic settings, which in turn are manifested through differences in plant ecology and rock surface weathering, respectively.